(untitled) (The Pakistan Development Review, 2004)
Highly subsidised public schools are the principal provider of education in the rural areas of Pakistan. Steady growth of school age population over time coupled with stagnant public funding has put enormous pressure on this system. The alternative of cost recovery through user charges has its own critics. They argue that introduction of tuition fees would substantially reduce the already small representation of low-income households in primary schools due to high price elasticity of their demand for schooling. Moreover, the revenuegenerating potential of this policy may also be limited due to same reason. The present study uses a discrete choice random utility model of household utility maximising behaviour to evaluate feasibility and consequences of introducing user fees in primary schools in rural Pakistan, particularly with reference to above criticisms. The demand function for school enrolment derived from this model allows us to test the hypothesis that price elasticity of demand for schooling varies with income. It also provides estimates of the parameters of the utility function needed for measuring parents’ willingness to pay for their childrens’ education if money generated from tuition fees is reinvested in education. The estimated demand function takes into account total price of education, including opportunity cost. Estimation results show that price elasticity of demand for school enrolment is higher for lower-income groups. Hence school enrolment of the poorest children would bear the main brunt of user fees policy. Children’s gender and age, father’s education, presence of T.V. in the household, and community variables like the presence of an elected district council member, electricity, and public transport in the village turn out to be significant influences on the probability of primary school enrolment. Willingness to pay for education is lower for poorer households and can generate revenues to cover only a fraction of the cost of running a school. Hence the need to search for other sources of financing primary education in rural Pakistan.